2011
DOI: 10.1002/ejic.201100756
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationship between Calcite–Gelatine Composites and Biogenic (Human) Otoconia

Abstract: Biogenic otoconia (ear dust) are composite materials of calcite with about 2 wt.-% proteins showing an average longitudinal size of about 10 μm. The tiny biomineral particles are situated in the inner ear (in the maculae) and act as sensors for gravity and linear acceleration. Our comparative study of calcite-gelatine composites (grown by double diffusion) and human otoconia is based on decalcification experiments, scanning electron microscopy, TEM and X-ray investigations in order to obtain a complete picture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 35 publications
1
48
1
Order By: Relevance
“…The X-ray powder pattern of biomimetically grown otoconia also confirms the presence of calcite as the inorganic component [25]. Completely developed specimens of biomimetic and biogenic (human) otoconia were glued on glass capillaries for investigation by single crystal X-ray methods [25,26]. Optical micrographs of the individuals together with the respective Bragg diffraction patterns are shown in Fig.…”
Section: Biomimetic Morphogenesis and Bulk Characterization In Relatimentioning
confidence: 88%
See 2 more Smart Citations
“…The X-ray powder pattern of biomimetically grown otoconia also confirms the presence of calcite as the inorganic component [25]. Completely developed specimens of biomimetic and biogenic (human) otoconia were glued on glass capillaries for investigation by single crystal X-ray methods [25,26]. Optical micrographs of the individuals together with the respective Bragg diffraction patterns are shown in Fig.…”
Section: Biomimetic Morphogenesis and Bulk Characterization In Relatimentioning
confidence: 88%
“…Biomimetic otoconia were grown by double-diffusion in gelatin-gel matrices [25,26]. The horizontal tubes of the U-shaped diffusion cells were filled with gelatine-gel while the vertical tubes contained aqueous solutions (pH = 7.4) of CaCl 2 , and Na 2 CO 3 , respectively.…”
Section: Biomimetic Morphogenesis and Bulk Characterization In Relatimentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the belly is dissolved first while the branches are attacked at later stages. The sequences of anisotropic dissolution clearly reveal the hierarchical inner architecture of otoconia consisting of 3+3 branches and a surrounding belly as shown in Figure 1a [4][5][6]11].…”
Section: Discussionmentioning
confidence: 99%
“…The nano-sized calcite component of human otoconia is intergrown with a small amount of organic material (<5%) forming the composite structure. Recent studies have revealed the inner structure of human otoconia consisting of a hierarchical architecture with a dumbbell-shaped dense area (branches) surrounded by a less dense, more porous structure (belly) (Figures 1a and 1b) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%